THE INFLUENCE OF SERVICE QUALITY AND DESTINATION IMAGE ON INTEREST IN REVISITING VISITOR SATISFACTION AS A MEDIATION VARIABLE - Revan Alfaredo; Reni Yuliviona; Zeshasina Rosha; Dahliana Kamener; Yuhelmi Yuhelmi (Jurnal Apresiasi Ekonomi, 2024)
This research aims to prove the influence of service quality and destination image on interest in revisiting visitor satisfaction as a mediating variable in a case study at the Gandoriah Pariaman Beach tourist attraction. This research uses a quantitative approach. The population in this study is all people who have visited the Gandoriah Pariaman Beach tourist attraction with a sample size of 100 respondents. Samples were taken using a purposive sampling technique. The results of this research were assisted by SPSS 26 and Smart-PLS 3. The results of this research can be concluded that the variables of service quality and visitor satisfaction have a positive effect on interest in revisiting, service quality has a positive impact on visitor satisfaction, and the destination image variable has no effect on interest in returning to visit. and visitor satisfaction. Another result is that the visitor satisfaction variable mediates the relationship between service quality and interest in revisiting and visitor satisfaction does not mediate the relationship between destination image and interest in reviewing.Keywords: Service Quality, Destination Image, Visitor Satisfaction, Intention to Revisit